Jackfruit (Artocarpus heterophyllus) seed powder supplementation helps to maintain metabolic homeostasis in both normal and high-sugar diet-fed mice (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: Diabetes mellitus and obesity stand as globally prevalent, life-threatening metabolic diseases. It has been reported that the intake of a high-sugar diet (HSD) increases the risk of developing diabetes and obesity. Therefore, it is necessary to find an alternative supplemental diet that could reduce the harmful consequences of excessive sugar consumption. The current study aimed to explore how jackfruit seed powder (JSP) could potentially prevent metabolic diseases in mice induced by an HSD. Materials and Methods: Swiss albino male mice were categorized into six groups fed normal and HSDs with or without JSP supplementation for 8 weeks. After the end of the feeding trial, different parameters related to glucose and lipid homeostasis were measured. Results: We found that 20% of JSP supplementation significantly decreased food intake and body weight gain induced by HSD. Supplementation of JSP reduced the liver weight, white adipose tissue, and brown adipose tissue weight in HSD-fed mice. Moreover, the addition of JSP with HSD improved the glucose tolerance test and reduced the levels of total cholesterol, triglyceride, and low-density lipoprotein cholesterol. Conclusion: These findings indicate that adding 20% JSP is particularly efficient in averting the onset of metabolic diseases induced by an HSD.J. Adv. Vet. Anim. Res., 12(2): 374–384, June 2025http://doi.org/10.5455/javar.2025.l905